Co-infection of Hepatitis A Virus with Salmonella Typhi (KYAMC Journal, 2022)
Waterborne diseases are very common in developing countries like Bangladesh due to intake of contaminated water from local water supply authority, along with inadequate sewage and water drainage systems. Multiple infections can occur with contaminated water. Viral hepatitis and typhoid fever are endemic in our country. Both are transmitted feco‐orally and are associated with poor sanitation, poor hygiene. Sometimes more than one type of infection along with coexisting febrile illness makes the diagnosis and management a challenging task. We report a case of 10 years young girl came to us with 10 days history of low grade intermittent fever, yellow discoloration of sclera and urine and right upper abdominal pain and final diagnosis was confirmed as co-infection of Hepatitis A and Salmonella typhi infection.KYAMC Journal. 2022;12(04): 250-251